AKURASI MESIN CNC ROUTER LOW BUDGET BERBASIS MACH 3 - Puguh Elmiawan; Dharmanto Dharmanto; Adik S.W; M Fazalul M; Arief R (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2022)
This paper discusses the building of a low-cost CNC router machine. In designing a CNC machine using an electrical actuator as the driving force, we use a nema 23 stepper motor combined with a pitch 2 mm timing belt to drive the machine on the x and y axes. On the z-axis, we use a stepper motor and a linear screw to drive the machine. This machine is often used to cut and engrave wood, acrylic, and PCB objects. The design drawing that has been made on the PC is sent to the microcontroller using serial communication, then the CNC performs work on the thing according to the coordinates. The spindle will create a pattern on the thing automatically according to the design drawing. Measurement was made using a caliper with an accuracy of 0.05 mm. This CNC machine is performing duly as ordered by the mach3 micro controller. The machine test results show an accuracy value of 99.85% on the x-axis, 99.74% on the y-axis, and 99.12% on the z-axis.